Effect of an educational leaflet on the frequency of seat belt use and the rate of motor vehicle accidents during pregnancy in Japan in 2018: a prospective, non-randomised control trial with a questionnaire survey. Issue 9 (20th September 2019) - Morikawa, Mamoru; Yamada, Takashi; Kogo, Hiromasa; Sugawara, Masaki; Nishikawa, Akira; Fukushi, Yoshiyuki; Hirayama, Emi Kato; Ishioka, Shin-ichi; Watari, Hidemichi
Abstract : Objective: To determine whether an educational leaflet had any effect on seat belt use, seat preference and motor vehicle accidents rate during pregnancy in Japan. Design: Prospective, non-randomised control trial with a questionnaire survey. Setting: Eight obstetric hospitals in Sapporo, Japan. Participants: 2216 pregnant women, of whom 1105 received the leaflet (intervention group) and 1111 did not (control group). Interventions: Distribution of an educational leaflet on seat belt use to women in the intervention group. Primary outcome measures: The effect of an educational leaflet on seat belt use, each pregnant woman's seat preference and the women's rates of motor vehicle accidents rate during their pregnancies. To evaluate the effects, the intervention group's responses to the questionnaires were compared with those of the control group. Results: The proportion of subjects who always used seat belts during pregnancy was significantly higher in the intervention group (91.3%) than in the control group (86.7%; p=0.0005). Among all subjects, the percentage of women who preferred the driver's seat was lower during pregnancy (27.0%) than before pregnancy (38.7%), and the percentage of women who preferred the rear seat was higher during pregnancy (28.8%) than before pregnancy (21.0%). These two rates did not differ between two groups. Seventy-one women (3.2%) reported experiencing a motor vehicle accident during pregnancy. The motor vehicle accident rate for the intervention group (3.3%) was similar to that for the control group (3.2%). Conclusions: An educational seat belt leaflet was effective in raising the rate of consistent seat belt use during pregnancy, but it did not decrease the rate of motor vehicle accidents. The wearing of seat belts should be promoted more extensively among pregnant women to decrease rates of pregnancy-related morbidity and mortality from motor vehicle accidents.